System Identification of Multidimensional Shoulder Impedance During Volitional Contractions. Issue 28 (2015) - Lipps, David B.; Baillargeon, Emma M.; Ludvig, Daniel; Perreault, Eric J.
Abstract: The shoulder is stabilized by passive structures and active muscle forces, but it is unknown how these factors interact to regulate three-dimensional (3D) joint mechanics during volitional contractions. Therefore, the objective of this study was to quantify the 3D impedance of the shoulder. Nonparametric identification was used to determine model structure; these estimates were described well by 3D inertial, viscosity, and elastic parameterizations. Our results show the elastic component is anisotropic and dependent on the patterns of volitional activation. Importantly, the shoulder muscles provide significant mechanical coupling between different degrees of freedom. We conclude that quantitative assessments of 3D shoulder mechanics may provide a more complete description of joint function.